Elevated Circulating Interleukin-17 Levels in Patients with Systemic Lupus Erythematosus: A Meta-analysis. (17th August 2020) - Shen, Hui-Hui; Fan, Ye; Wang, Ya-Ni; Zhao, Chan-Na; Zhang, Zhi-Kang; Pan, Hai-Feng; Wu, Guo-Cui
ABSTRACT: Background: Previous studies concerning the circulating interleukin-17 (IL-17) in systemic lupus erythematosus (SLE) were contradictory. Aims: To further precisely investigate circulating IL-17 in SLE and evaluate its influential factors by meta-analysis. Methods: EMBASE, PubMed and Cochrane Library were comprehensively searched to obtain studies on circulating IL-17 in SLE patients by November 22, 2018. The results were illustrated by pooled standard mean difference (SMD) with corresponding 95% confidence interval (CI) using random-effects model as there was significant heterogeneity, which was estimated using Cochran Q and I 2 statistics. Subgroup analyses and sensitivity analyses were also conducted. Results: Overall, 1872 articles were reviewed and 20 studies involving 1067 subjects with SLE and 721 healthy controls (HCs) were enrolled in the final analysis according to inclusion criteria. Compared with HCs, circulating IL-17 levels in SLE patients were elevated (SMD: 1.183, 95% CI: 0.763–1.603; P < .001). Moreover, in comparison to HCs, European and Asian SLE patients, age <30 years, disease duration ≥5 years, NOS scores <7 and using ELISA showed increased circulating IL-17 status, whereas no significant change was observed in other subgroups. There was no significant publication bias. Sensitivity analyses demonstrated that the results of our meta-analysis were robust. Conclusions: SLE patients have higher circulating IL-17 levels, which is influenced by ethnic, age and disease duration, literature quality and measurements.